2012
DOI: 10.5333/kgfs.2012.32.1.15
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Growth Characteristics and Nutritional Components of Corn Hybrids for Silage at Paddy Field Cultivation

Abstract: This study was carried out to know adaptability and growth characteristics, yield, chemical compositions and nutrition yield of corn hybrids for silage at paddy field. The field experiments were conducted at Sangju province for one year (2009). The experimental design was arranged in a randomized block design with three replication. The treatments consisted of eleven corn hybrids. The planting date was on 1 May and harvested at 24 August. Stem diameter, stem hardness and number of ear were higher in P32P75 tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Generally it is being reported that mineral content is affected by weather conditions, soil conditions, manure conditions and other various conditions (Reid et al, 1970;Kim, 1991;Lee and Lee, 2010). However, it was a higher yield than the reports from Kim et al (2012) which reported that mineral content in 10 varieties of silage corn had a content range of 6,790 ~9,775 mg/kg, and Jeon et al (2012) which reported that the 9 varieties of Sorghum × Sudangrass hybrids had a content range of 6,222.6~15,020.5 mg/kg.…”
Section: Mineral Contentsmentioning
confidence: 92%
See 2 more Smart Citations
“…Generally it is being reported that mineral content is affected by weather conditions, soil conditions, manure conditions and other various conditions (Reid et al, 1970;Kim, 1991;Lee and Lee, 2010). However, it was a higher yield than the reports from Kim et al (2012) which reported that mineral content in 10 varieties of silage corn had a content range of 6,790 ~9,775 mg/kg, and Jeon et al (2012) which reported that the 9 varieties of Sorghum × Sudangrass hybrids had a content range of 6,222.6~15,020.5 mg/kg.…”
Section: Mineral Contentsmentioning
confidence: 92%
“…~6,499 mg/100g in barley (Lee and Kim, 2013), 3,653~5,433 mg/100g in silage corn (Kim et al, 2012), and 2,324~3,908 mg/100g in Sorghum × Sudangrass hybrids (Jeon et al, 2012). Therefore, it was shown that compared to barley, corn, and sorghum × sudangrass hybrids, Italian ryegrass had significantly higher amino acid content.…”
Section: Composition Amino Acid Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…그리고 중부지역에 재배가 용이하고 조숙성인 '소만' 품종을 개발하였으며, 최근에는 줄기에 잎귀가 없어 부드럽고 밀식에 강한 '다미' 품종을 개발 보급 하여 많은 축산 농가들이 이용하고 있다 (Kim et al, 2012c;. 또한 우리나라 사료작물용 으로 재배 이용하는 대표적인 청보리 품종은 위에서 설명 한 영양, 우호, 유연, 소만, 다미 품종을 들 수 있다.…”
Section: 이러한 원인으로 인하여 현재까지 국내 적응성이 높고unclassified
“…Thus, considerable information on amino acid profiles is required for domestically produced forages. In this regard, our laboratory has previously reported on the amino acid profiles of corn silage [30] and sorghum × sudangrass hybrids [31].…”
Section: Resultsmentioning
confidence: 99%